The Philosophy of Mulla Sadra Being a Summary of His Book al-Hikmah al-Muta’aliyah fi al-Asfar al-‘Aqliyyah al-Arba’ah - Hamid Fahmy Zarkasyi (TSAQAFAH, 2009)
The depiction of Mulla Sadra’s philosophy could be best out by referring to his magnum opus, al-Hikmah al-Muta’aliyah, usually referred to as al-Asfar alArba’ah. The book contains almost all aspect of philosophy such as theory of essence and existence, subtance, movement, time, world order, knowledge, intellect and the likes. In addition, being Muslim peripatetic, he also gives special interest on the demonstrating the concept of God and eschatology. The summary below could hopefully be instrumental for paying particular interest in further studying Mulla Sadra thought for academic pusposes. The point interest, however, is to be found in his repudiation againts Ibn Sina’s concept of Essence and Existence. Whereas Ibn Sina vindicates the essence rather than existence, Sadra gives priority to existence rather than essence. Not only has Mulla Sadra differed from Ibn Sina and other Muslim peripatetic on the issue of essence and existance, but also on the problem of substance, movement, time.